Survei Ketahanan Petani Sekitar Kawasan Industri Pengolahan Nikel di Sulawesi Tenggara - Rela, Iskandar Zainuddin; Mappasomba, Musadar (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
Exploration of mineral resources can encourage economic development and threaten the environment, health, ecosystem, and social comfort of the surrounding community. Therefore, through Corporate Social Responsibility (CSR) activities or other activities, industrial companies can balance negative impacts and strengthen sustainable development that can improve the resilience and welfare of the surrounding community. Therefore, this research aims to assess the community's resilience in supporting the sustainability of agricultural development. The research will be conducted in Morosi Subdistrict, Konawe Regency. The concept of community resilience and the theory of sustainability of growth became the basis of this study. This research was started by conducting literature studies in various reputable books and journals to determine community resilience dimensions. Finally, set 5 dimensions measuring community resilience and six indicators measure the sustainability of agricultural development. A total of 24 items are used to measure community resilience and six instruments to measure the sustainability of agricultural development. This research was conducted from October to December 2020. The study involved 295 respondents distributed to family heads in 10 villages adjacent to Nickel Industry activities. Descriptive Statistical Analysis is used to explain the level of resilience of the community. This study found that farmers' resilience was built due to the operation of the nickel industry at the research site, such as economic dimensions, social capital, environment, community competence, information, and communication. The dimensions of social capital, community competence, knowledge, and communication are considered high. In comparison, the economic and environmental aspects are relatively moderate. This dimension is expected to be one of the guidelines for the government in taking a policy of building farmers community' resilience for the sustainability of agricultural development, especially farmers around the Nickel mining industry.